Population structuring of the endemic black-cheeked gnateater, Conopophaga melanops melanops (Vieillot, 1818) (Aves, Conopophagidae), in the Brazilian Atlantic Forest - VO. Lunardi; MR. Francisco; PM. Galetti Jr. (Brazilian Journal of Biology)
Randomly amplified polymorphic DNA (RAPD) markers were used to analyze genetic differentiation among three populations of the endemic Black-cheeked Gnateater (Conopophaga melanops melanops) within a larger pristine reminiscent of the Brazilian Atlantic Forest. Analyses of molecular variance (AMOVA) (phiST = 0.13149, P < 0.0001) and the nonparametric test for homogeneity of the molecular variance (HOMOVA) (B = 0.32337; P = 0.0019) showed a statistically significant genetic divergence among the three Black-cheeked Gnateater populations in a continuous transect of 250 km. Some hypothetic explanations for these results are the sedentary nature of the species and the historical isolation of the populations in refuges during the Pleistocene. The present results suggest that the local populations were naturally differentiated along the entire original range before the recent process of massive deforestation.